Isolation and Identification of Porcine Epidemic Diarrhea Virus and Its Effect on Host Natural Immune Response - Qian, Shaoju; Zhang, Weida; Jia, Xiangchao; Sun, Zhijian; Zhang, Yang; Xiao, Yuncai; Li, Zili (Frontiers in Microbiology, 2019)
Porcine epidemic diarrhea (PED) is a highly infectious intestinal disease caused by porcine epidemic diarrhea virus (PEDV). A PEDV strain was isolated from the piglet intestinal tract in Vero cells in Jiangsu Province, designated as the JS-A strain. PEDV was identified as the isolated virus by cytopathology, immunofluorescence assay, western blotting, transmission electron microscopy, and sequence analysis. The full-length genome of JS-A isolate and the S gene were systematically analyzed, indicating that PEDV JS-A belongs to the G2a subtype, which is closely related to the prevalent PEDV in many countries and different from many current vaccines. Animal regression tests showed that piglets that are orally infected with the virus continue to develop diarrhea with yellowish and unpleasant odors. Further, piglets showed reduced food consumption and weight loss in the challenged group, while there were no abnormalities in the control group. In addition, Toll-like receptors (TLRs), RIG-I, and the downstream medium gene in the intestinal mucosa of newborn pigs infected with PEDV JS-A strain were studied. The neonatal Fc receptor (FcRn) was the only IgG transport receptor and protected IgG from degradation. Therefore, PEDV JS-A infection might inhibit FcRn expression by down-regulating TLRs and downstream signaling molecules. Taken together, isolation of the JS-A variant contributes to evolutionary analysis of the diarrhea virus. Further, the experimental infection model lays a foundation for further research related to vaccine development and the antiviral natural immune response of infected piglets, which helps us better understand PEDV pathogenesis and immune mechanism.